Product Line Analysis - Aprilliantoni, Aprilliantoni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
The objective of this study was to assess the impact of product lines, pricing, and promotions on consumer decisions to get consumer credit facilities in Jakarta banking. A marketing objective's success or failure is contingent on a variety of elements. Product lines, pricing, and promotions impact the buying choice of a consumer or, in this example, a customer's decision to get a consumptive credit facility. The research strategy employed is the correlation technique. Correlational research tries to identify whether or not there is a link between two or more variables and the extent of the correlation between the variables analyzed. As research objectives, 100 respondents who were Banking in Jakarta consumer credit customers were sampled through the distribution of a set of statements or questionnaires to acquire information directly from respondents. This research employs a quantitative approach to analysis. This strategy attempts to transform data into information in the form of numbers. This study use SPSS for data processing. In this study, the hypothesis being tested is related to the influence of the independent variable on the dependent variable. H0 is a hypothesis that shows no effect and HA is a hypothesis for the research conducted. Keywords: Consumer Credit; Price; Promotion; Product Line